2020
DOI: 10.1136/jech-2020-214021
|View full text |Cite
|
Sign up to set email alerts
|

Association between industry payments for opioid products and physicians’ prescription of opioids: observational study with propensity-score matching

Abstract: BackgroundIndustry marketing to physicians for opioids has received substantial attention as it can potentially influence physicians’ prescription of opioids. However, robust evidence demonstrating a causal link between industry payments for opioids and physicians’ prescription practice for opioids is lacking.MethodsUsing the national databases of physicians treating Medicare beneficiaries, we examined the association between physicians’ receipt of opioid-related industry payments in 2016 and (1) the number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 28 publications
(34 reference statements)
2
23
0
Order By: Relevance
“…In this context, our findings focusing on long-acting insulin (which constitutes a large proportion of insulin prescriptions and expenditures in the US [20]) generate a hypothesis that physician-industry financial relationship may increase the overall costs of long-acting insulin for patients with diabetes, which works against the national effort to reduce the patients' financial burden of using insulin. Although our data do not adjudicate the appropriateness of the prescription, it may also be possible that industry marketing payments introduce physicians' preference of prescribing long-acting insulin rather than cheaper, oral antihyperglycemic therapies that may be equally effective in some clinical situations, given the prior literature on this topic [4][5][6][7]. More investigations are warranted for long-acting insulins to avoid unnecessary prescriptions of this costly and common drugs that affect millions of Americans with diabetes.…”
Section: Plos Medicinementioning
confidence: 79%
See 1 more Smart Citation
“…In this context, our findings focusing on long-acting insulin (which constitutes a large proportion of insulin prescriptions and expenditures in the US [20]) generate a hypothesis that physician-industry financial relationship may increase the overall costs of long-acting insulin for patients with diabetes, which works against the national effort to reduce the patients' financial burden of using insulin. Although our data do not adjudicate the appropriateness of the prescription, it may also be possible that industry marketing payments introduce physicians' preference of prescribing long-acting insulin rather than cheaper, oral antihyperglycemic therapies that may be equally effective in some clinical situations, given the prior literature on this topic [4][5][6][7]. More investigations are warranted for long-acting insulins to avoid unnecessary prescriptions of this costly and common drugs that affect millions of Americans with diabetes.…”
Section: Plos Medicinementioning
confidence: 79%
“…As a part of the Affordable Care Act, since 2013, the Open Payments program has mandated that medical product manufacturers publicly report all payments to physicians and teaching hospitals [ 3 ]. Previous studies have documented associations between industry payments and prescriptions for specific drugs including opioids [ 4 , 5 ] and cardiovascular drugs [ 6 , 7 ]. Some studies also showed that even the receipt of meals—the most frequent and inexpensive type of industry payments [ 8 ]—was associated with an increased rate of prescriptions of drugs from the sponsoring manufacturer [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The financial relationship between physicians and the pharmaceutical industry has received substantial attention as it may affect physicians’ clinical practice [ 14 , 15 ]. Since the launch of the Open Payments program under the Physician Payment Sunshine Act which requires the pharmaceutical industry to publicly report data on all payments and ownership interests made to licensed physicians and teaching hospitals in 2013 [ 16 ], a growing body of literature linking the financial physician-industry relationship with physicians’ prescriptions of opioids has been published [ 17 21 ]. All previous studies consistently showed the association between the receipt (or the number of encounters) of industry marketing payments at a single time point and an increased number of opioid prescriptions.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, several studies revealed that junior physicians, more so than senior physicians, were more likely to accept interactions with Pharma [ 85 , 86 ] and consider them appropriate and valuable [ 86 ]. Therefore, we would suggest that all medical schools establish a curriculum on FCOI addressing these relationships’ undue influence on clinical practice [ 6 , 69 , 87 ] and their impact on patient trust and care [ 73 ]. Given that even preclinical medical students can interact with Pharma, it might be advisable to implement this curriculum early, by the second or third year in Japan [ 77 , 88 , 89 ].…”
Section: Clinical Implementationmentioning
confidence: 99%